Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di Era Digital - Arif Rahman; Nurjanah Nurjanah; Rahyuni Rahyuni; Risna Purwanti (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
In the era of digital transformation, technology plays a central role in shaping the future of education. This study explores the role of school principals as transformative leaders in promoting technology-based learning, particularly in the context of Indonesian schools. Using a descriptive qualitative approach, data were collected through in-depth interviews with school principals, teachers, and education personnel from schools that have integrated technology into their teaching and learning processes. Secondary data were obtained from government policies, official school documents, and relevant literature. Thematic analysis was employed to identify key patterns related to leadership practices that support the adoption of educational technology. The findings reveal that effective principals act not only as visionaries and change agents but also as facilitators, mentors, and collaborators who foster inclusive and innovative school environments. They play a critical role in developing teachers’ digital competencies, ensuring adequate infrastructure, and building a positive digital culture. This study highlights the importance of strategic leadership in overcoming challenges such as limited resources and resistance to change. The results provide practical guidance for principals and policymakers to develop sustainable technology-based education programs and contribute to the global discourse on educational leadership in developing countries. Keywords: , , , , .